Public-and-Private Partnership Institutionalization of Ukrainian Natural Resource Potential Capitalization in Decentralization - YUKHYMENKO, Petro; SOKOLSKA, Tetyana; GRINCHUK, Julia; ZUBCHENKO, Victoria; KHAKHULA, Bohdan; DZHEGUR, Gennadii; LOBACHOVA, Svitlana (Journal of Environmental Management and Tourism, 2022)
The paper studies the process of using natural resource potential in a new decentralized environment considering its variability and problems of national economy and rural areas, exacerbation of exogenous threats to economic self-sufficiency and economic security of the country as well as local self-government reforms on the sample of Ukraine. The necessity of forming a perfect institutional environment that improves the investment climate of rural areas, opens opportunities for accelerated capitalization of natural resource potential of newly created communities and the development of private-public partnership between the state and business structures. The formation of a new institutional environment for the development of public-private partnership and management decentralization will contribute to the capitalization of natural and economic assets owned by state and rural communities. The necessity of normative-legal expansion of the list of spheres of application of public-private partnership agreements is substantiated and the expediency of clear identification of all possible forms of relations between state and private partners based on the implementation of positive foreign experience is emphasized. The necessity of public-private partnership agreements as a factor of strengthening economic and financial self-sufficiency of newly created territorial communities in the conditions of decentralization of power strengthening and local self-government reformation is proved.